Accounting of Refinancing and Take Over for Murabahah Contract - Kunaifi, Aang; Handayati, Puji; Bahri, Mat (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The development of community needs necessitates the dynamics of services at Islamic financial institutions, especially in contract schemes or transaction models. Besides being influenced by the financial capacity of the community, there is also a rational choice to get cheaper transaction options. So, in the practice of Islamic finance, refinancing and take over transaction schemes are also developing. This article was written with the aim of describing the accounting treatment of refinancing transactions and taking over for murabahah contracts and analyzing them based on sharia compliance (sharia compliance). The research approach used is the literature on fiqh laws as guidelines for sharia compliance which has been regulated in the DSN MUI fatwa. The findings that the author can convey in this article are that there are several rational reasons for the recognition and treatment of PSAK-based accounting which regulates refinancing and take over transactions with the obligation to recognize the existence of margins in both transactions. Meanwhile, in fiqh, there is actually a deviation from compliance with sharia.